Airport Cargo Logistics and Economic Outcome of Supply Chain: An Empirical Analysis - Yacoub Hamdam (International Journal of Supply Chain Management, 2020)
Abstract Purpose – The United Arab Emirates (UAE) will have the third largest international air cargo market in the world by 2018 according to a new report by the International Air Transport Association (IATA). Handling airport cargo in and along with the integrated supply chain has become increasingly challenging in a competitive environment, particularly in Abu Dhabi. In this perspective, the purpose of the study is to investigate the influence of five factors-price sensitivity, cost leadership, airport charges, provision of unique product and services, development of airport facilities on competitive advantage. Design/Methodology/approach – An online questionnaire link sent to 168 airport logistics executives, out of which 102 respondents submitted. A convenience sampling method was used and the statistical software PLS was employed to measure the suitability of the conceptual framework. Findings – All the five factors or independent variables are positively related to the dependent variable, which confirms the support to the conceptual framework and hypothesis through various statistical analyses. Managerial Implications – Managers need to understand the relationship of the five factors, which are positively related to the dependent variable. Designing, developing and delivering on all the constructs as promised to the stakeholders are vital to achieve competitive advantage. Originality/Value – Due to lack of empirical research work in airport logistics, particularly in UAE, this study will be value added research work and fills the research gap as well. Keywords: Cargo logistics, Competitive advatage, Cost leadership, Airport charges, Product and service, Abu Dhabi, UAE